2022
DOI: 10.2460/ajvr.21.12.0205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canine raw food products for the presence of extended-spectrum beta-lactamase- and carbapenemase-producing bacteria of the order Enterobacterales

Abstract: OBJECTIVE To assess the potential contamination of commercial raw dog food products with bacteria of the Enterobacterales order that produce extended spectrum beta-lactamase (ESBL) and carbapenemase enzymes, determine risk factors for contamination, and understand isolate genetic diversity. SAMPLES A total of 200 canine raw food products. METHODS Products were cultured on selective chromogenic agar following enrichment steps. Whole-genome sequencing was performed for isolates that were confirmed to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 54 publications
3
10
0
Order By: Relevance
“…RDF sold in the UK is mostly stored frozen prior to preparation for consumption, and most owners believe that the freezing process kills bacteria (Morgan et al 2022). However, as is clearly evident from this study and others (Morgan et al 2024, Cole et al 2022, Davies et al 2019) ABR E. coli are present in defrosted RDF, which likely explains epidemiological findings that feeding RDF is associated with an increased likelihood that dogs excrete ABR bacteria (Groat et al 2022, Runesvard et al 2020, Davies et al 2019, Lefebvre et al 2008, Sealey et al 2022, Sealey et al 2023).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…RDF sold in the UK is mostly stored frozen prior to preparation for consumption, and most owners believe that the freezing process kills bacteria (Morgan et al 2022). However, as is clearly evident from this study and others (Morgan et al 2024, Cole et al 2022, Davies et al 2019) ABR E. coli are present in defrosted RDF, which likely explains epidemiological findings that feeding RDF is associated with an increased likelihood that dogs excrete ABR bacteria (Groat et al 2022, Runesvard et al 2020, Davies et al 2019, Lefebvre et al 2008, Sealey et al 2022, Sealey et al 2023).…”
Section: Discussionsupporting
confidence: 64%
“…For RDF, a study in the USA reported 10% of samples positive for ESBL-producing Enterobacterales, of which 76% were E. coli . Pork RDF had the highest sample-level positivity (38%) for ESBL-producers, followed by beef (10%), and chicken (7%) (Cole et al 2022). A recent survey in the UK on RDF report 14% of samples were positive for ESBL-producing E. coli , 47% of these positive samples were RDF stated as being made from offal/tripe, 33% from chicken, 17% beef, and 17% lamb, though it should be noted most samples were mixed protein sources with 67% of the offal based RDF contained chicken (Morgan et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding of raw diets is a rapidly growing trend with substantial concern regarding both the development of food‐borne disease in pets and the risk to humans handling raw food products and in contact with animals fed such diets and their environment 12 . Several dangerous pathogens with zoonotic capacity have been identified in commercial raw food diets and raw meat, including extended‐spectrum β‐lactamase producing Enterobacterales , Salmonella species, Clostridium perfringens and several other bacterial and protozoal pathogens 12‐15 . Biliary H. heydorni in the dog described here may represent a novel unusual infectious disease related to feeding of raw meat, but both the source of infection and the pathogenicity of H. heydorni in our case cannot be definitively proven.…”
Section: Discussionmentioning
confidence: 91%
“…12 Several dangerous pathogens with zoonotic capacity have been identified in commercial raw food diets and raw meat, including extendedspectrum β-lactamase producing Enterobacterales, Salmonella species, Clostridium perfringens and several other bacterial and protozoal pathogens. [12][13][14][15] Biliary H. heydorni in the dog described here may represent a novel unusual infectious disease related to feeding of raw meat, but both the source of infection and the pathogenicity of H. heydorni in our case cannot be definitively proven.…”
Section: Discussionmentioning
confidence: 99%
“…Raw meat can become contaminated with pathogens during slaughter, processing and transportation and there is existing evidence of RMBD cross-contamination during manufacturing ( 1 , 6 , 10 ). Previous studies have detected DNA from undeclared protein sources in RMBDs and genetically-identical bacteria has been isolated from RMBDs with different protein sources that were produced by the same manufacturer ( 10 , 11 ). Salmonella species are often a prominent concern, as these bacteria cause 26,500 hospitalizations in the United States annually ( 12 ).…”
Section: Introductionmentioning
confidence: 99%